Manajemen Kurikulum Pendidikan Anak Usia Dini Berbasis Alam Di TK Saymara Sukoharjo - YOEWONO, Haryono, Prof. Dr. Sutama, M.Pd (2015)
This study was to describe and illustrate as clearly as possible on: (1) The activity management functions related to the implementation of early childhood curriculum in kindergarten Saymara Sukoharjo 2013/2014 school year for class B (2) the extent to which the use of nature into teaching materials (3) differences in curriculum management TK Saymara Sukoharjo with Conventional kindergarten curriculum management. The method of case studies including a qualitative descriptive study. Data collection techniques using observation, in-depth interviews and documentation. Analysis of the research data used to draw conclusions is an interactive model analysis. The object of research is the activity management functionality curriculum for early childhood education kindergarten Saymara Sukoharjo. Based on the results of data analysis can be summarized as follows: (1) activity in the kindergarten curriculum management functions based nature in Saymara Sukoharjo include (a) planning (b) organizing (c) implementation (d) evaluation. In any activity management functions contain nature-based education curriculum development indicators love of nature which is a typical indicator of the nature school. 2) differences in kindergarten curriculum management Saymara Sukoharjo with conventional kindergarten curriculum management is reflected in the curriculum components include (a) learning objectives (b) teaching materials (c) learning method (d) evaluation (e) setting environment. The components in nature school curriculum let learners being closer to nature by making nature as a learning environment in learning activities.